Experiences of UIN Alauddin Library Data Migration from the Old System to A New One - Taufiq Mathar; Andi Marwansyah; Feri Ardinata (Literatify: Trends in Library Developments, 2020)
Currently, many libraries have implemented library automation systems or integrated library system. The conventional services are replaced by technology-based services. This article describes the experience of Alauddin UIN Library in migrating data from the old to a new system. This descriptive study uses a case study approach. The data were obtained from observations and experiences of the library staff involved during the migration processes. The study showed that the system transition was carried out because the old system had experienced several obstacles, migrating data required established planning. In addition, the library must also consider the time, cost, funds, and competent human resources. The hardest obstacle faced by the library during migration was in the data conversion section in which there were differences in data structures between the two systems. This study can be used as a reference for other libraries that planning to migrate to a new library system.ABSTRAKSaat ini banyak perpustakaan telah menerapkan sistem otomasi perpustakaan. Pelayanan konvensional digantikan dengan pelayanan berbasis teknologi. Artikel ini menggambarkan pengalaman Perpustakaan UIN Alauddin memigrasikan datanya dari sistem lama ke sistem yang baru. Penelitian deskriptif ini menggunakaan pendekatan studi kasus. Data diperolah dari hasil pengamatan dan pengalaman orang-orang yang terlibat dalam proses migrasi data dari sistem yang lama ke sistem yang baru. Hasil penelitian menunjukkan bahwa peralihan sistem dilakukan karena sistem lama telah mengalami beberapa kendala, migrasi data ke sistem yang baru memerlukan perencanaan yang mapan. Selain itu, perpustakaan juga harus mempertimbangan waktu, biaya, dana, dan juga sumber daya manusia yang kompeten. Kendala terberat yang dihadapi perpustakaan ketika migrasi ada pada bagian konversi data di mana terdapat perbedaan struktur data antar kedua sistem. Kajian ini dapat dijadikan sebagai salah satu rujukan bagi perpustakaan-perpustakaan yang hendak melakukan migrasi data.